Distributed Cognition in J.S. Khairen's Novel Bungkam Suara: Technogenesis and the Engineering of Collective Cognition in the Perspective of Hayles' Posthumanism - Mariana Maharuju; Ellyana Hinta; Herman Didipu (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
The digital age has changed the way humans think, but Indonesian literature studies still rarely read about this cognitive transformation as a distributed system involving humans and technology. This article analyzes the representation of distributed cognition in J.S. Khairen's  novel Silence of Voices  using the technogenesis framework of  N. Katherine Hayles, focusing on how a character's cognition transcends the boundaries of the body and is distributed into media networks, information systems, and surveillance technologies. Through a qualitative-narrative analysis approach, the findings show that distributed cognition in the novel is a form  of technogenesis that is also a mechanism for engineering collective cognition. Technology no longer functions as a neutral tool, but rather as an agent that directs—even determines—the way characters perceive the truth, form identities, and respond to information. Engineering strategies include information control through geo-fencing, the production of public opinion through engineered pro-con scenarios, and mass mobilization through digital command systems. This article argues that when cognition is distributed into systems that are not controlled by the individual, technology goes from an emancipatory tool to a subtle but effective social control mechanism. The theoretical contribution of this article is to expand the application of  Hayles' technogenesis in the study of contemporary Indonesian literature and show that this novel functions as a posthumanist critique of digital subjectivity.